The Roles of ATP13A2 Gene Mutations Leading to Abnormal Aggregation of α-Synuclein in Parkinson’s Disease - Zhang, Fan; Wu, Zhiwei; Long, Fei; Tan, Jieqiong; Gong, Ni; Li, Xiaorong; Lin, Changwei (Frontiers in Cellular Neuroscience, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease. PARK9 (also known as ATP13A2) is recognized as one of the key genes that cause PD, and a mutation in this gene was first discovered in a rare case of PD in an adolescent. Lewy bodies (LBs) formed by abnormal aggregation of α-synuclein, which is encoded by the SNCA gene, are one of the pathological diagnostic criteria for PD. LBs are also recognized as one of the most important features of PD pathogenesis. In this article, we first summarize the types of mutations in the ATP13A2 gene and their effects on ATP13A2 mRNA and protein structure; then, we discuss lysosomal autophagy inhibition and the molecular mechanism of abnormal α-synuclein accumulation caused by decreased levels and dysfunction of the ATP13A2 protein in lysosomes. Finally, this article provides a new direction for future research on the pathogenesis and therapeutic targets for ATP13A2 gene-related PD from the perspective of ATP13A2 gene mutations and abnormal aggregation of α-synuclein.